Patients, Protocols, and Prosocial Behavior: Rule Breaking in Frontline Health Care - Borry, Erin L.; Henderson, Alexander C. (American review of public administration, 2020)
Rules are essential components of organizations, especially given their foundational role in inducing organizationally preferred behavior and reducing behavioral variability among its members. Despite the existence and prevalence of these centrally important tools, rule deviation occurs. This study proposes to understand the ways in which emergency medical service (EMS) professionals break rules for prosocial purposes—to help patients. In particular, this research seeks to understand how specific organizational and personal attributes influence rule-breaking tendencies. Results indicate that aspects of ethical climate are significantly related to prosocial rule-breaking (PSRB) tendencies, whereas empathy is not. In addition, this study finds that other characteristics, such as a conformist personality, risk taking, expertise, and experience on the job influence PSRB. These findings contribute to the literature on rule deviation and EMS practices and shed light on the complexity of decision making in frontline public services.